2013
DOI: 10.1186/2040-7378-5-13
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependence of sensorimotor and cerebral electroencephalographic asymmetry in rats subjected to unilateral cerebrovascular stroke

Abstract: BackgroundThe human population mostly affected by stroke is more than 65 years old. This study was designed to meet the recommendation that models of cerebral ischemia in aged animals are more relevant to the clinical setting than young animal models. Until now the majority of the pre-clinical studies examining age effects on stroke outcomes have used rats of old age. Considering the increasing incidence of stroke among younger than old human population, new translational approaches in animal models are needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
(91 reference statements)
1
8
0
1
Order By: Relevance
“…Due to the lack of consensus in the evolution of the contralateral side, an asymmetric index is often used to reflect changes of rhythms in both hemispheres over time. This asymmetry calculated by the brain symmetry index (BSI) or the global pairwise derived brain symmetry index (pdBSI) is also present in experimental studies as reported during both acute (1 h post-stroke) and chronic phases (up to 14 days post-stroke) in young and one-year-old rats, respectively [ 161 ].…”
Section: Eeg In Stroke Conditionsmentioning
confidence: 81%
See 2 more Smart Citations
“…Due to the lack of consensus in the evolution of the contralateral side, an asymmetric index is often used to reflect changes of rhythms in both hemispheres over time. This asymmetry calculated by the brain symmetry index (BSI) or the global pairwise derived brain symmetry index (pdBSI) is also present in experimental studies as reported during both acute (1 h post-stroke) and chronic phases (up to 14 days post-stroke) in young and one-year-old rats, respectively [ 161 ].…”
Section: Eeg In Stroke Conditionsmentioning
confidence: 81%
“…Thus, ischemia has resulted in an increase of low frequency and a decrease of high frequency oscillations, or specifically a decrease of the α-to-δ ratio [ 17 , 159 ], considering the baseline distribution as 25%–45% of δ, 40% of θ, 12%–15% of α, and 3%–20% of β oscillations [ 16 , 17 ]. In particular, an increase in δ power in the ipsilateral hemisphere after transient MCA stroke was reported in both the subacute and chronic phase from 24 h to seven days or beyond [ 16 , 17 , 160 , 161 , 162 , 163 ]. Another study reported that an increase of the ipsilateral δ and θ power occurred as early as one minute following intraluminal filament occlusion of the proximal part of MCA that leads to impairment in the subcortical brain regions [ 164 ].…”
Section: Eeg In Stroke Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…В проведенных ранее исследованиях показано, что ишемическое повреждение мозга, даже локальное, может привести к его глобальной дисфункции, что находит свое отражение в нарушениях его нейронной активности [17]. Так, нарушения сознания, вызванные острыми эпизодами гипоперфузии мозговой ткани, сопровождаются диффузным увеличением мощности τ-и δ-активности с угнетением низко-и среднечастотного компонентов α-ритма, при этом усугубление гипоксии приводит к увеличению мощности δ-ритма и снижению мощности τ-и α-ритмов [18].…”
Section: Discussionunclassified
“…Having in mind that epidemiological studies revealed that human stroke occurs more often in late middle age (50–70 years) than at older ages (more than 70 years) it comes as quite a surprise that young animals are mostly used to test new drugs for stroke. By now, however, there is a number of reports on age-related alterations in the response to stroke at transcriptional, cellular, and electrophysiological level [ 11 , 13 , 14 , 15 , 16 , 17 , 18 ]. Therefore, extrapolating results from young animals to aged humans could lead to erroneous conclusions [ 19 , 20 ].…”
Section: Age As An Important Factor In Preclinical Studies Of Stromentioning
confidence: 99%